전기전도도 측정을 통한 반류수 MLE공정에서 공기공급 제어기술 개발 - 장신요(Shinyo Chang); 신풍식(Pung Shik Shin); 정연구(Yeon-Koo Jeong); 최영준(Young June Choi) (Daehan hwan'gyeong gonghag hoeji, 2020)
목적:반류수를 대상으로 무산소조에서 전기전도도 측정을 통해 호기조의 공기공급량을 제어할 수 있는 기술을 개발하여 공정성능 향상 및 에너지 사용량 절감을 달성하고자 하였다. 방법:전기전도도가 생물학적처리의 운전지표로 활용될 수 있는지를 검증하기 위해 각 공정별 수질인자와 전기전도도의 상관성 분석을 여름철(메탄올 투입), 겨울철, 가을철 시기로 나누어 실험하였다. 기존에 제시된 필요공기량 수식을 간단히 정리하여 경험식을 제시하고, 이를 활용해 전기전도도 범위에 공기공급량을 순차적으로 넣어 조견표를 작성하였다. 성능평가는 암모니아성질소와 총무기질소의 제거효율, SNR과 SDNR, 공기공급량의 변화, 유입수 변화에 대한 공정의 안정성 등을 기준으로 판단하였다. 결과 및 토의:계절별로 전기전도도와 각 수질항목의 상관계수가 0.5267~0.9115 범위로 암모니아성질소, 총무기질소, DOC, 인산염인 순서로 높게 산출되었다. 상관계수 0.5 이상으로 생물학적 처리공정의 운전지표로 전기전도도가 활용될 수 있음을 알 수 있었다. 전기전도도와 암모니아성질소의 회귀식은 계절별로 재현성이 확보되어 전기전도도를 통해 암모니아성질소를 추정하는 것이 가능할 것으로 판단된다. 호기조 말단 DO가 3.4 mg/L 정도에서 겨울철 질소처리효율이 가장 양호하였다. 호기조 DO는 공기공급량으로 제어할 수 있으며 질소와 상관성이 높은 전기전도도를 직접 측정하여 공기공급량을 제어하고 질소처리효율을 향상시키는 것이 가능함을 알 수 있었다. 전기전도도와 유입유량을 통해 필요공기량을 산정할 수 있는 경험식을 제시하였고, 식 계수를 구한 결과 A', (B' + X')는 각각 0.0589 (m3-air/h)/(m3/h)/(µS/cm), -77.562 (m3-air/h)/(m3/h)로 나타낼 수 있었다. 겨울철기간 무산소조의 전기전도도 측정값에 따라서 공기공급량을 자동 제어한 결과는 총무기질소 제거효율과 SDNR이 실플랜트 조건보다 각각 8.3%, 0.007 g-N/g-MLSS/d 높게 나타났다. 자동제어한 기간 동안에 공기공급량/유입유량 평균비가 36 (m3-air/h)/(m3/h)로 실플랜트 조건보다 공기공급량을 21.7% 감소시킬 수 있었다. 결론:전기전도도 기반 MLE공정의 공기공급 제어기술은 질소제거 효율 향상 및 에너지 사용량 절감을 동시에 달성할 수 있을 것으로 판단된다. Objectives:This study aimed to achieve improved process performance and energy saving by developing a technology to control the air supply of an aerobic basin by measuring the conductivity in the anoxic basin. Methods:To verify whether conductivity can be used as an operation indicator of biological treatment, the correlation analysis between water quality factor and conductivity of each process was conducted by dividing into summer (methanol input), winter and autumn periods. An empirical formula was presented by briefly arranging the required air quantity formula, and a quick reference was prepared by putting air supply in the conductivity range sequentially. The performance evaluation was judged based on the removal efficiency of ammonia nitrogen and total inorganic nitrogen, SNR and SDNR, the change of air supply, the stability of the process against inflow change. Results and Discussion:The seasonal correlation coefficients of conductivity and water quality items were calculated in the order of ammonia nitrogen, total inorganic nitrogen, DOC, and phosphate in the range of 0.5267~0.9115. It was found that the conductivity could be used as an operation indicator of the biological treatment process with a correlation coefficient of 0.5 or more. The regression equations for the conductivity and ammonia nitrogen are secured by season, so it is possible to estimate the ammonia nitrogen through the conductivity. At the end of the aerobic basin DO was 3.4 mg/L, the nitrogen treatment efficiency in winter was the best. The aerobic basin DO can be controlled by the air supply, and it can be seen that it is possible to control the air supply and improve the nitrogen treatment efficiency by directly measuring the conductivity having a high correlation with nitrogen. An empirical formula for estimating the required air volume through conductivity and inflow is presented. A' and (B' + X') are 0.0589 (m3-air/h)/(m3/h)/(µS/cm) and -77.562 (m3-air/h)/(m3/h) The result of automatic control of air supply according to the measured conductivity of anoxic tank during winter season showed that total inorganic nitrogen removal efficiency and SDNR were 8.3% and 0.007 g-N/g-MLSS/d higher than actual plant conditions, respectively. During the automatic control period, the air supply/inflow average ratio was 36 (m3-air/h)/(m3/h), which could reduce the air supply by 21.7% compared to the actual plant conditions. Conclusions:The air supply can be estimated from the flow rate and conductivity. The air supply control technology of the conductivity-based MLE process will be able to simultaneously improve nitrogen removal efficiency and reduce energy consumption. KCI Citation Count: 0